Analisa Pengaruh Asset (NPL) dan Likuiditas (LDR) Terhadap Return Saham Perbankan Go Public di Indonesia - Popon Rabia Adawia; Alfatih S. Manggabarano (Universitas Bina Sarana Informatika, 2020)
Abstract - This study was conducted to examine the influence of fundamental factors (NPL, and LDR) on stock returns Banks listed in the Indonesia Stock Exchange for the period 2005-2014. The sampling technique used in this research is purposive sampling with criteria as follows, 1) Listed in Indonesia Stock Exchange in 2005-2014, 2) Always report the annual financial statements during the period from 2005 to 2014, 3) is engaged in the same relative industry. Data required in this study were taken from Indonesian Capital Market Directory (ICMD), during 2005-2014 has listings for 42 companies banking and samples taken 10 Bank. Multiple regression analysis of data by the method of ordinary least squares (OLS). Hypothesis test used t-statistic and f-statistics at 5% significance level. The results showed Non perfoming loan (NPL) and loan to deposit ratio (LDR) significantly affects stock returns. The results of this study indicate that the performance factors fundamental Non perfoming loan (NPL) and loan to deposit ratio (LDR) should be considered to increase the Return Stocks, because by keeping the balance between the funds raised to be channeled into loans and for NPL small or well then will produce maximum profit. Keywords: Non perfoming Loan, Loan to Deposit Ratio and Stock Return